2001
DOI: 10.1093/clinchem/47.10.1776
|View full text |Cite
|
Sign up to set email alerts
|

Tau and Aβ42 in Cerebrospinal Fluid from Healthy Adults 21–93 Years of Age: Establishment of Reference Values

Abstract: Background: Tau protein and the 42-amino acid form of β-amyloid (Aβ42) measured in cerebrospinal fluid (CSF) have been proposed as potential biochemical diagnostic markers for Alzheimer disease. For the introduction of these assays in clinical practice, adequate reference values are of importance. Methods: CSF samples were obtained from 231 neurologically and psychiatrically healthy individuals, 21–93 years of age, all with a MiniMental State examination score of 28 or above. Standardized ELISAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
227
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(254 citation statements)
references
References 40 publications
22
227
0
5
Order By: Relevance
“…The removal of Zn(II) induced Ab fibrillization in our experiments. However, at low physiological Ab concentrations 0.11 nmol/L in brain (Sjogren et al 2001) the fibrillization of monomeric Ab is a slow and unlikely process. It is repeatedly demonstrated that introduction of Ab 42 into brain cannot induce amyloid formation in vivo (Meyer-Luehmann et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The removal of Zn(II) induced Ab fibrillization in our experiments. However, at low physiological Ab concentrations 0.11 nmol/L in brain (Sjogren et al 2001) the fibrillization of monomeric Ab is a slow and unlikely process. It is repeatedly demonstrated that introduction of Ab 42 into brain cannot induce amyloid formation in vivo (Meyer-Luehmann et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The increased CSF tau in the bulbar-onset patients is explained by the higher mean age of this specific group. It has been shown in fact that there is an increase of CSF tau in normal aging which may reflect a physiological mild progressive neuronal degeneration [12]. Furthermore, we took all precautions in order to reduce the risk of an artifactual change of the CSF tau level, such as the use of polypropylene tubes, storage of CSF samples at)80°C, and avoiding freezing-thawing procedures [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in fact that there is an increase of CSF tau in normal aging which may reflect a physiological mild progressive neuronal degeneration [12]. Furthermore, we took all precautions in order to reduce the risk of an artifactual change of the CSF tau level, such as the use of polypropylene tubes, storage of CSF samples at)80°C, and avoiding freezing-thawing procedures [12]. In addition, we did not analyze in this study of CSF samples (either from ALS cases or controls) a measured total protein falling outside the higher normal cut-off level given by our laboratory (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Cerebrospinal fluid levels of total s, phosphorylated s, and amyloid-b were normal. 17 Neurological examination was normal. DAT imaging showed decreased uptake in the right and left putamen ( Fig.…”
Section: Case Reportmentioning
confidence: 97%